1998
DOI: 10.1002/(sici)1097-4636(199822)43:2<153::aid-jbm9>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial properties of self-reinforced composite poly(methyl methacrylate)

Abstract: Total joint prostheses are often fixed in the bone using bone cement. The cement mantle, however, is prone to fatigue fracture that can lead to failure of the mantle, evolution of bone cement particles, and eventual loosening and failure of the prosthesis. A new material, self-reinforced composite poly(methyl methacrylate) (SRC-PMMA) was developed previously by the authors. This material has a similar chemical composition to bone cement, with the matrix and reinforcing fibers both fabricated from PMMA. One pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…In biomedical applications, self‐reinforced poly(methyl methacrylate) (SRC‐PMMA) has been investigated as a potential pre‐coat material for total hip replacements 2–9. Studies have shown that uni‐axial SRC‐PMMA has a significant increase in tensile strength, tensile modulus, fatigue strength, and tensile strain to failure 9.…”
Section: Introductionmentioning
confidence: 99%
“…In biomedical applications, self‐reinforced poly(methyl methacrylate) (SRC‐PMMA) has been investigated as a potential pre‐coat material for total hip replacements 2–9. Studies have shown that uni‐axial SRC‐PMMA has a significant increase in tensile strength, tensile modulus, fatigue strength, and tensile strain to failure 9.…”
Section: Introductionmentioning
confidence: 99%
“…SRC‐PMMA can be woven around a hip prosthesis, or other irregularly shaped object, and incorporated into a composite using hot compaction 25. This precoat has significantly enhanced mechanical properties over PMMA, and could hypothetically enhance the performance of the femoral component at the metal–bone cement interface.…”
Section: Introductionmentioning
confidence: 99%
“…Stellbrink et al [19] also studied the processing technique as applied to a liquid crystalline copolyester with the interesting result that the compacted LCP fibers exhibited high impact energy absorption, although the influence of compaction conditions on impact resistance was not clarified. Wright and coworkers [20,21] used hot compaction to prepare composites from poly(methyl methacrylate), PMMA, for biomedical applications, revealing substantial improvements in flexural, tensile, fracture toughness, and fatigue properties of compacted PMMA specimens compared to the virgin materials.…”
Section: Introductionmentioning
confidence: 99%